The Rise and Fall of the Tahrir Repertoire: Theorizing Temporality, Trajectory, and Failure. (6th July 2020) - Said, Atef
Abstract: This article examines how and why the strategy of occupying Tahrir Square went from being the central mode of action and defining image of the Egyptian Revolution of 2011 to an ineffective strategy read by many as symbolic of the revolution's ultimate failure during the transitional period of 2011–2012. This question speaks to a lacuna in the literature on repertoires, specifically a lack of attention to their temporality and the lessons to be learned from their failure. I propose a framework that examines the trajectory of repertoires and traces their 1) meaning; 2) internal composition; 3) relationality vis-à-vis the regime in relation to which the repertoire is practiced; and 4) temporal momentum. Using this framework, I chart the rise and fall of the Tahrir repertoire in a very short period: from February 12, 2011, to December 5, 2012. The article draws on ethnographic, qualitative, and historical data collected over three research trips taken between February 4, 2011, and January 7, 2015.